PENGENALAN HIDROPONIK DAN PUPUK ORGANIK CAIR DI KALANGAN PEREMPUAN PEKERJA KEBERSIHAN POLITEKNIK NEGERI SAMARINDA - Nadir, Mardhiyah; Rahim, Marinda; yana, Fitri; Pangestu, Galih; Fadilan, Amjat (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2022)
Female cleaning service employees at Politeknik Negeri Samarinda (Polnes) are mostly housewives with low-grade education and working to help their husbands to increase their income. Their income will be increased as long as they have the knowledge and skill to produce other businesses such as organic nutrients and hydroponic organic vegetable plants from garbage or waste. This community service activity was held at the Politeknik Negeri Samarinda campus’ nearby area with training and practice methods. 15 female cleaning service workers on this campus., The first session was subject to making liquid organic fertilizer using waste materials from Terminalia catappa L. leaves and banana peels which are fermented using EM-4 bacteria and brown sugar nutrients which are used as organic nutrients for hydroponic plant. Meanwhile, the second session was subject to making hydroponicmedia from waste materials such as mineral water glass packaging, mineral water bottles, used Styrofoam from fruit or rice packaging, and wasted flannel. At the end of the community service activity, the participants had a well understanding of making liquid organic fertilizer and hydroponic media.Keywords: garbage, hydroponic, liquid organic fertilizer Abstrak Pekerja perempuan yang menjadi pegawai cleaning service di Politeknik Negeri Samarinda (Polnes) mayoritas merupakan pekerja perempuan rumah tangga berpendidikan rendah, yang bekerja untuk membantu suami guna menambah penghasilan keluarga. Penghasilan pekerja perempuan petugas cleaning service ini dapat ditingkatkan jika mereka memiliki pengetahuan untuk membuat nutrisi organik serta tanaman sayur organik hidroponik yang dapat dijual dengan memanfaatkan bahan utama yang sudah menjadi sampah atau limbah yang dengan mudah dapat diperoleh oleh pekerja perempuan tersebut. Peserta terdiri dari 15 orang pekerja perempuan cleaning service di Polnes. Sesi pertama merupakan materi untuk membuat pupuk organik cair dengan menggunakan bahan sampah daun ketapang dan kulit pisang yang difermentasi menggunakan bakteri EM-4 dan nutrisi gula merahyang digunakan sebagai nutrisi organik untuk tanaman hidroponik. Sedangkan sesi kedua merupakan materi pembuatan media hidroponik dari bahan-bahan limbah seperti kemasan gelas air mineral, botol air mineral, styrofoam bekas kemasan buah atau nasi, dan kain perca bekas. peserta pelatihan telah sangat memahami cara membuat pupuk organik cair dan media hidroponik.Kata kunci: hidroponik, pupuk organik cair, sampah organik